2017
DOI: 10.3390/su9030357
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Field Application of Red Clay Green Roof Vegetation Blocks for Ecological Restoration Projects

Abstract: Abstract:In this study, for restoration of ecological systems in buildings, porous vegetation red clay green roof blocks were designed for performance evaluation. Blast furnace slag (BFS; fine aggregates (agg.)), coarse aggregates, polyvinyl alcohol (PVA) fiber (hydrophilic fiber), and red clay (ecofriendly additive material) were applied to the construction of the porous vegetation red clay green roof blocks. A decrease in cement use is one way of reducing carbon emissions. To increase the water retentivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…For example, numerous studies have shown that the depth of the substrate influences the capacity for rainwater retention [33,37]. In relation to the geometric characteristics of a roof, some researchers have tried to establish relationships between the slope of the roof and the amount of runoff retained [38,39], while others have analysed the reduction in runoff according to the type of vegetation installed on the green roof [40][41][42][43]. This paper will contribute to those studies by proving empirically how much runoff water could be reduced by installing different types of green roofs around frequently flooded areas.…”
mentioning
confidence: 99%
“…For example, numerous studies have shown that the depth of the substrate influences the capacity for rainwater retention [33,37]. In relation to the geometric characteristics of a roof, some researchers have tried to establish relationships between the slope of the roof and the amount of runoff retained [38,39], while others have analysed the reduction in runoff according to the type of vegetation installed on the green roof [40][41][42][43]. This paper will contribute to those studies by proving empirically how much runoff water could be reduced by installing different types of green roofs around frequently flooded areas.…”
mentioning
confidence: 99%